Working Memory, Processing Speed, and Memory Functioning Are Minimally Predictive of Victoria Symptom Validity Test Performance. (September 2021) - Resch, Zachary J.; Soble, Jason R.; Ovsiew, Gabriel P.; Castillo, Liliam R.; Saladino, Kevin F.; DeDios-Stern, Samantha; Schulze, Evan T.; Song, Woojin; Pliskin, Neil H.
A sound performance validity test is accurate for detecting invalid neuropsychological test performance and relatively insensitive to actual cognitive ability or impairment. This study explored the relationship of several cognitive abilities to several performance indices on the Victoria Symptom Validity Test (VSVT), including accuracy and response latency. This cross-sectional study examined data from a mixed clinical sample of 88 adults identified as having valid neurocognitive test profiles via independent validity measures, and who completed the VSVT along with objective measures of working memory, processing speed, and verbal memory during their clinical neuropsychological evaluation. Results of linear regression analyses indicated that cognitive test performance accounted for 5% to 14% of total variance for VSVT performance across indices. Working memory was the only cognitive ability to predict significant, albeit minimal, variance on the VSVT response accuracy indices. Results show that VSVT performance is minimally predicted by working memory, processing speed, or delayed verbal memory recall.